2016
DOI: 10.1051/0004-6361/201628421
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of active region outflows throughout an active region lifetime

Abstract: Context. We have shown previously that SOHO/UVCS data allow us to detect active region (AR) outflows at coronal altitudes higher than those reached by other instrumentation. These outflows are thought to be a component of the slow solar wind. Aims. Our purpose is to study the evolution of the outflows in the intermediate corona from AR 8100, from the time the AR first forms until it dissolves, after several transits at the solar limb. Methods. Data acquired by SOHO/UVCS at the time of the AR limb transits, at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Upflowing plasma is observed by Hinode/EIS in approximately the same locations for at least 8-9 days as ARs transit the solar disk (Démoulin et al, 2013). Recently, Zangrilli and Poletto (2016) have shown that the upflows persist for much longer periods. Using data from Solar and Heliospheric Observatory's Ultraviolet Coronagraph Spectrometer (SOHO/UVCS), they demonstrated that upflows from AR 8100 extended into the intermediate corona to become outflows and persisted for the AR's entire lifetime which spanned five solar rotations.…”
Section: General Characteristics Of Active Region Upflowsmentioning
confidence: 87%
“…Upflowing plasma is observed by Hinode/EIS in approximately the same locations for at least 8-9 days as ARs transit the solar disk (Démoulin et al, 2013). Recently, Zangrilli and Poletto (2016) have shown that the upflows persist for much longer periods. Using data from Solar and Heliospheric Observatory's Ultraviolet Coronagraph Spectrometer (SOHO/UVCS), they demonstrated that upflows from AR 8100 extended into the intermediate corona to become outflows and persisted for the AR's entire lifetime which spanned five solar rotations.…”
Section: General Characteristics Of Active Region Upflowsmentioning
confidence: 87%
“…3. Images and spectra of active regions show rapid flows with speeds of at least 100 km s −1 along their fanned-out edges (e.g., Harra et al 2008;Brooks and Warren 2011;Morgan 2013;Zangrilli and Poletto 2016). The slow solar wind associated with these structures may come from small, short-lived coronal holes adjacent to the active regions themselves ).…”
Section: Periodicities Linking the Sun And Heliospherementioning
confidence: 99%
“…There are also investigations of the long-term (time scales covering a full AR lifetime or more) evolution of, e.g the magnetic influence of AR plasma flows (e.g. Harra et al 2017;Zangrilli andPoletto 2016 andKo et al 2016), the CME production rate along the solar cycle (e.g. Gopalswamy et al 2003 andRiley et al 2006), the global magnetic field and its associated CME production (Petrie, 2013), and the continuous tracking of some AR magnetic properties (e.g.…”
Section: Introductionmentioning
confidence: 99%